Isolation and toxin typing of clostridium perfringens from Sungai Selangor and Sungai Bernam / Florence Lee Chi Hiong - Lee, Florence Chi Hiong (2009)
Clostridium perfringens (CP) is an anaerobic, spore forming bacterium that is emerging as a preferred faecal pollution indicator. In the local scene, little is known about the density and toxinotype of CP in river water, and how does river discharge affects the density. Therefore, water samples were taken from three Malaysian rivers, Sungai Bernam, Sungai Selangor and Tengi Canal between April 2007 and January 2008 to examine the CP densities and toxinotypes. The rivers were selected because of their differences in adjacent land usage. Sungai Selangor reported lower CP isolation rate ranging between 0 to 25% but higher CP densities of <1 to 2695 cfu/100ml. In contrast, CP isolation rates in Sungai Bernam were higher at 0 to 35% but the densities were lower at <1 to 763 cfu/100ml. Tengi Canal showed the lowest CP isolation rate of 0 to 10% and CP densities of <1 to 212 cfu/100ml. Sulphite reducing Clostridia (SRC) were consistently present, and the densities were significantly different temporally in each of the study sites. The highest CP and SRC densities were in the downstream of Sungai Selangor. No significant correlation was found between CP densities and river discharge in all the study sites. Toxinotyping was performed with Polymerase Chain Reaction (PCR) using published primer sequences, and multiplex primers designed specifically to include also the detection of enterotoxin (CPE) gene. All 142 CP isolates found in this study belonged to Clostridium perfringens Type A. Five of the isolates also harboured CPE gene.